Genome-Wide High-Resolution aCGH Analysis of Gestational Choriocarcinomas - Poaty, Henriette; Coullin, Philippe; Peko, Jean Félix; Dessen, Philippe; Diatta, Ange Lucien; Valent, Alexander; Leguern, Eric; Prévot, Sophie; Gombé-Mbalawa, Charles; Candelier, Jean-Jacques; Picard, Jean-Yves; Bernheim, Alain (PLOS ONE, 2012)
Eleven samples of DNA from choriocarcinomas were studied by high resolution CGH-array 244 K. They were studied after histopathological confirmation of the diagnosis, of the androgenic etiology and after a microsatellite marker analysis confirming the absence of contamination of tumor DNA from maternal DNA. Three cell lines, BeWo, JAR, JEG were also studied by this high resolution pangenomic technique. According to aCGH analysis, the de novo choriocarcinomas exhibited simple chromosomal rearrangements or normal profiles. The cell lines showed various and complex chromosomal aberrations. 23 Minimal Critical Regions were defined that allowed us to list the genes that were potentially implicated. Among them, unusually high numbers of microRNA clusters and imprinted genes were observed.